2020
DOI: 10.1101/2020.04.10.035543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neutrophil antimicrobial peptide cathelicidin promotes Th17 differentiation

Abstract: The host defence peptide cathelicidin (LL-37 in humans, mCRAMP in mice) is released from neutrophils by de-granulation, NETosis and necrotic cell death; it has potent antibacterial, antiviral and antifungal activity as well as being a powerful immunomodulator. It is released in proximity to CD4 + T cells during inflammatory and infectious disease but its impact on T cell phenotype is scarcely understood. Here we demonstrate that cathelicidin is a powerful Th17 potentiating factor which increases expression of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 94 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…The fact that they induce T cell activation and proliferation has not previously been demonstrated; however, our data supports work showing that individual intracellular neutrophil mediators can promote T cell differentiation and inflammatory cytokine production. For example, lactoferrin promotes Th1 generation in concert with BCG vaccination ( 44 ) and increases T cell cytokine production during infection with Staphylococcus aureus ( 45 ); the neutrophil alpha defensins induce NFkb signalling in T cells ( 46 ); and the granule peptide cathelicidin promotes Th17 differentiation ( 21 ) and activates CD8 + T cells ( 47 ). However, all of these interpretations must be made in light of the fact that NETotic neutrophils did not activate the T cells, but rather suppressed as significantly as resting cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that they induce T cell activation and proliferation has not previously been demonstrated; however, our data supports work showing that individual intracellular neutrophil mediators can promote T cell differentiation and inflammatory cytokine production. For example, lactoferrin promotes Th1 generation in concert with BCG vaccination ( 44 ) and increases T cell cytokine production during infection with Staphylococcus aureus ( 45 ); the neutrophil alpha defensins induce NFkb signalling in T cells ( 46 ); and the granule peptide cathelicidin promotes Th17 differentiation ( 21 ) and activates CD8 + T cells ( 47 ). However, all of these interpretations must be made in light of the fact that NETotic neutrophils did not activate the T cells, but rather suppressed as significantly as resting cells.…”
Section: Discussionmentioning
confidence: 99%
“…An extra layer of complexity is provided by the fact that not only intact neutrophils, but also their released mediators, can affect T cell behavior. For example, exocytosis of certain anti-microbial and/or cytotoxic molecules such as myeloperoxidase and arginase-1 have been shown to suppress T cell proliferation ( 18 20 ), and we have recently shown that neutrophil-derived cathelicidin can skew T cell differentiation towards a Th17 phenotype and promote survival ( 21 ). Furthermore, release of neutrophil extracellular traps (NETs) can directly prime human CD4 + T cells by reducing their activation threshold so that they can respond to suboptimal stimulation ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, during asthma exacerbation, another work has found increased levels of IL-17A from nasal lining fluid and increased frequency of Th17 cells in peripheral blood of asthmatic patients (66,98). One of the characteristics of those who had virus-driven asthma exacerbation was high sputum neutrophils that have shown to skew the polarization of naïve T cells to Th17 cells via neutrophil antimicrobial peptide cathelicidin (155,156). A recent prospective study identified a causal relationship between circulating IL-6 and asthma exacerbations, which could be plausibly explained by IL-6-driven differentiation of naïve T cells into Th17 cells that trigger asthma exacerbation (157).…”
Section: The Role Of Th1 Th2 and Th17 Cells In Asthma Exacerbationmentioning
confidence: 99%
“…These structures trap proximal microbes and use the bound AMPs to kill or prevent bacterial and fungal growth. Within viable resting cells, AMPs, including defensins and cathelicidins, typically localize in cytoplasmic granules [63][64][65][66] and calprotectin in the cytoplasm [67,68].…”
Section: Microbes Drive the Development Of Innate Oral Immunitymentioning
confidence: 99%